2013
DOI: 10.1155/2013/380614
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Black Carbon Aerosol Sources in the East Baltic Region

Abstract: One-year continuous measurements of aerosol black carbon (BC) at the background site Preila (55°55′N, 21°00′E, 5 m a.s.l., Lithuania) were performed. Temporal and spatial evolution and transport of biomass burning (BB) and volcanic aerosols observed within this period were explained by the air mass backward trajectory analysis in conjunction with the fire detection data produced by the MODIS Rapid Response System and AERONET database. The surface measurements and analysis of the Angström exponent of the absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
4
0
1
Order By: Relevance
“…Atmospheric BC can be emitted by combustion processes from anthropogenic activities, natural fires or volcanoes. 30 A background atmospheric BC concentration of 0–0.02 μg m −3 , indicating the absence of combustion emissions in aerosols, is recorded along most of the voyage track except aerosols A8 to A11 and aerosol A1. Aerosols A8 to A11 are associated with BC concentrations between 0.04–0.15 μg m −3 .…”
Section: Resultsmentioning
confidence: 99%
“…Atmospheric BC can be emitted by combustion processes from anthropogenic activities, natural fires or volcanoes. 30 A background atmospheric BC concentration of 0–0.02 μg m −3 , indicating the absence of combustion emissions in aerosols, is recorded along most of the voyage track except aerosols A8 to A11 and aerosol A1. Aerosols A8 to A11 are associated with BC concentrations between 0.04–0.15 μg m −3 .…”
Section: Resultsmentioning
confidence: 99%
“…The highest BC concentrations were registered in the Baltic Sea in the area of intensive shi pping and situated close to areas with dense population (up to 258 ng/m 3 in sample 8 and 261 ng/m 3 in sample 11). BC concentrations in the Baltic Sea in June of 2011 have been reported to be 280 ng/m 3 on average [21]. Emission sensitivities calculated with FLEXPART showed that these high concentrations are probably attributed to anthropogenic BC originating from Northern European countries, rather than biomass burning in Eurasia.…”
Section: Resultsmentioning
confidence: 99%
“…where B can be either B abs or B scat and AE can be either AAE or SAE. AAE and SAE are calculated by fitting exponential curves on the measured B abs and B scat , respectively [68,69].…”
Section: Preprocessing Absorption and Scattering Measurementsmentioning
confidence: 99%